Effect of tool rotational speeds on material flow and strain rates during friction stir butt welding of AA2219-T87 plates - Bagadi R.M.; Jaidi J.; G M K.; G P.K.R. (My University, 2025)
Friction stir welding (FSW) process is widely used for joining Al-Cu alloy (AA2219-T87) plates because of its high joint efficiency and low residual stresses in contrast to fusion-based joining techniques. A two-way coupled, 3D thermal-material flow model has been developed in COMSOL software, and the effect of tool rotational speeds on thermal and material flow fields, strain rates, thermal histories, and size of weld zones are being studied. The non-uniform net heat generation during the FSW process is due to the friction between workpiece and tool materials and the deformation energy of plasticized material flow sheared by the rotating tool. An approximate range of temperatures for the weld zones has been proposed and found to be appropriate because the predicted sizes are in good agreement with the experiments. Furthermore, the authors suggested that a quality FSW joint must have the nugget zone smaller and the heat-affected zone larger than the tool shoulder diameter. © 2024 Informa UK Limited, trading as Taylor & Francis Group.